Composite photocatalysts containing MIL-53(Fe) as a heterogeneous photo-Fenton catalyst for the decolorization of Rhodamine B under visible light irradiation - Vo, Dai-Viet N.; Nguyen, Vinh Huu; Bach, Long Giang; Bui, Quynh Thi Phuong; Nguyen, Trinh Duy; Vu, Hien Thi; Do, Sy Trung (Elsevier Ltd, 2018)
The development of composite photocatalyst is a promising direction for improving photocatalytic performance of decomposition of organic dyes. This study aimed to fabricate two composite photocatalysts using either Fe3O4 or NiFe2O4 with MIL-53(Fe) as heterogeneous catalysts for the degradation of rhodamine B (RhB) under visible light irradiation by a 40 W compact fluorescent lamp. The physicochemical, the surface, the magnetic and the energy band gap of the photocatalyst were characterized by XRD, FT-IR, Raman, FE-SEM, UV-vis DRS, Brunauer-Emmett-Teller (BET), and VSM. From the photocatalytic activities test results, the NiFe2O4-doped MIL-53(Fe) sample expressed a higher photocatalytic degradation capacity of RhB than that of Fe3O4/MIL-53(Fe) sample, significantly better than that of the bare of Fe3O4, NiFe2O4, and MIL-53(Fe).